Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376548
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Twitter Users Who Engage in Adversarial Interactions against Political Candidates

Abstract: Social media provides a critical communication platform for political figures, but also makes them easy targets for harassment. In this paper, we characterize users who adversarially interact with political figures on Twitter using mixed-method techniques. The analysis is based on a dataset of 400 thousand users' 1.2 million replies to 756 candidates for the U.S. House of Representatives in the two months leading up to the 2018 midterm elections. We show that among moderately active users, adversarial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Since then, the model has been retrained on a larger dataset and modified to address some of its weaknesses reported by other researchers (e.g., [45]). Several other studies have used the Perspective API and have demonstrated that its predictions are accurate [28,42].…”
Section: Toxicity Annotationsmentioning
confidence: 99%
“…Since then, the model has been retrained on a larger dataset and modified to address some of its weaknesses reported by other researchers (e.g., [45]). Several other studies have used the Perspective API and have demonstrated that its predictions are accurate [28,42].…”
Section: Toxicity Annotationsmentioning
confidence: 99%
“…To measure the degree of attack conveyed by tweets toward others on Twitter, we employed Google's Perspective API 11 , a popular tool widely used for online abuse and harassment study [16,17,35]. The perspective API allows users to measure the toxicity of a text in English on a scale from 0 to 1.…”
Section: Measurement Of Toxicitymentioning
confidence: 99%
“…On the other hand, we have to note that there were fewer tweets with very high toxicity overall (e.g., tweets with toxicity scores above 0.7[16,17] or 0.5[18]), regardless of the cluster.…”
mentioning
confidence: 95%
“…Partisans are also much more likely to share fact-checking messages that denigrate their political opponents and boost their political allies [53]. Highly active partisans are also more likely to engage in adversarial interactions with out-party politicians on Twitter [26,27].…”
Section: Partisanship and Online Behaviormentioning
confidence: 99%
“…Understanding the role of partisanship in social media interactions is integral to improving online platforms. For example, partisanship underscores potentially harmful online behavior such as toxic political discourse and harassment of counter-partisan politicians and members of the public [26,27,34]. Political misinformation on social media has been linked to dire offline consequences such as the January 6 United States Capitol attack [48].…”
Section: Introductionmentioning
confidence: 99%